Preparation method of special graphite and special graphite

CN122916670APending Publication Date: 2026-10-16BAOWU CHARCOAL MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610946825.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]由上可知,上述专利均存在“高强度-低膨胀系数”难以兼顾的技术瓶颈

Benefits of technology

[0007] To address the aforementioned technical problems, embodiments of the present invention disclose a method for preparing special graphite and the special graphite thereof.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a preparation method of special graphite and the special graphite. The preparation method comprises the following steps: distillation: high-temperature coal tar is subjected to distillation to obtain soft pitch; first coking: the soft pitch is subjected to coking to obtain binding coke and coking light oil; second coking: the binding coke is subjected to coking to obtain green coke and coking heavy oil; calcination: the green coke is subjected to calcination in an oxygen-containing atmosphere to obtain calcined coke; first mixing: the binding coke and the calcined coke are mixed as a precursor; second mixing: the coking light oil and the coking heavy oil are mixed as an additive; kneading: the precursor and the additive are mixed and then subjected to kneading to obtain a paste; the paste is subjected to a forming process, a baking process and a graphitization process in sequence to obtain the special graphite; wherein the volatile content of the binding coke is 10-40%, and the coking value is greater than or equal to 80%; and the aspect ratio of the calcined coke is greater than or equal to 1.58. The obtained special graphite has high flexural strength and low thermal expansion coefficient, and realizes closed-loop resource utilization of raw materials and simple process flow.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of special graphite technology, and particularly to a method for preparing special graphite and the special graphite itself. Background Technology

[0002] Specialty graphite, also known as high-strength, high-density, and high-purity graphite, refers to graphite products possessing these characteristics. It exhibits physicochemical properties such as high-temperature resistance, thermal shock resistance, corrosion resistance, good electrical conductivity, and good lubricity, making it a key basic material in high-end manufacturing fields such as photovoltaics, semiconductors, new energy batteries, aerospace, nuclear engineering, and the military industry. In particular, specialty graphite includes high-end specialty graphite, which requires graphite products to possess both excellent mechanical properties and a low coefficient of thermal expansion.

[0003] In the prior art, CN118580073A discloses a graphite crucible for crystal growth furnaces and its preparation method. It uses self-sintering raw materials as the main material and a composite material of high thermal conductivity graphene and pitch coke powder as a microstructure regulator. The graphite crucible for crystal growth furnaces is prepared through isostatic pressing, carbonization, and graphitization. This patent relies on the use of graphene as an external reinforcing phase, and the resulting graphite product has a flexural strength of 70-80 MPa and a coefficient of thermal expansion of 5.5 × 10⁻⁶. -6 ℃ -1 ~6.3×10 -6 ℃ -1 .

[0004] CN122010566A discloses a preparation process and application of isostatically pressed special graphite products made from artificial graphite powder. The process involves using calcined petroleum coke / asphalt coke as raw material, undergoing pre-graphitization treatment as a special aggregate, and combining it with a binder system containing nano-carbon materials through liquid-phase composite processing, cold isostatic pressing, and a single calcination to obtain isostatically pressed special graphite. The nano-carbon materials are carbon nanotubes and / or graphene. This patent relies on the use of carbon materials as an external reinforcing phase, resulting in special graphite with a flexural strength of 67-84 MPa and a coefficient of thermal expansion of 3.7 × 10⁻⁶. -6 ℃ -1 ~5.3×10 -6 K -1 .

[0005] CN116462509A discloses an isostatically pressed graphite for photovoltaic applications, its preparation method, and its application. Using petroleum coke, pitch coke, and carbon black as aggregates, and adding modified pitch and modified carbon fibers, the process involves kneading, secondary grinding, pressing, calcination, impregnation, secondary calcination, and graphitization to obtain the isostatically pressed graphite for photovoltaic applications. This patent relies on the use of modified carbon fibers as an external reinforcing phase and still requires two calcinations and one impregnation. The resulting special graphite has a flexural strength of 56-61 MPa and a coefficient of thermal expansion of 8.2 × 10⁻⁶. -6 ℃ -1~9.7×10 -6 ℃ -1 .

[0006] As can be seen from the above, all of the aforementioned patents suffer from the technical bottleneck of achieving both high strength and low coefficient of thermal expansion simultaneously. Furthermore, they typically rely on external reinforcing phases (such as graphene, carbon fibers, and carbon nanotubes) to compensate for the porosity defects in graphite products and improve their mechanical properties. However, these external reinforcing phases are all introduced from external sources, leading to poor structural compatibility between the aggregate and the external reinforcing phase. Some existing technologies even rely on multiple impregnation-calcination cycles (usually 2-4 times), resulting in complex process routes and high production costs. Summary of the Invention

[0007] To address the aforementioned technical problems, embodiments of the present invention disclose a method for preparing special graphite and the special graphite thereof.

[0008] In a first aspect, embodiments of the present invention provide a method for preparing special graphite, comprising:

[0009] Distillation: Soft pitch is obtained by distilling high-temperature coal tar.

[0010] First coking: The soft asphalt is coked to produce caking coke and coking light oil;

[0011] Second coking: Coking the clumped coke to produce raw coke and coking heavy oil;

[0012] Calcination: Raw coke is calcined in an oxygen-containing atmosphere to obtain calcined coke;

[0013] First mixing: The binder coke and the calcined coke are mixed as a precursor;

[0014] Second mixing: Light coking oil and heavy coking oil are mixed as an additive;

[0015] Mixing: The precursor and additives are mixed and kneaded to obtain a paste;

[0016] Special graphite is obtained by sequentially processing the paste through molding, calcination, and graphitization processes.

[0017] Among them, the bonding coke has volatile matter and coking value. The volatile matter of the bonding coke is 10~40%, and the coking value is ≥80%; the aspect ratio of the calcined coke is ≥1.58.

[0018] By adopting the above technical solution, the obtained special graphite has both high flexural strength and low coefficient of thermal expansion, and realizes closed-loop resource utilization of raw materials with a simple process flow.

[0019] Furthermore, in the first coking step, the coking temperature is 350~450℃, the coking time is 2~8h, and the coking pressure is 0.1~0.3MPa.

[0020] Furthermore, in the second coking step, the coking temperature is 450~520℃, the coking time is 6~24h, and the coking pressure is 0.1~0.3MPa.

[0021] Furthermore, the temperature is increased from the first coking step to the second coking step at a rate ≥40℃ / h.

[0022] Furthermore, in the calcination step, the calcination temperature is 1000~1500℃, and the calcination time is 0.5~8h.

[0023] Furthermore, in the first mixing step, the bonded coke and the calcined coke are crushed and ground separately until the particle size D of the bonded coke is reduced. 50 After the particle size of the calcined coke is ≤5μm and the particle size of the calcined coke is 5~500μm, it is mixed at a mass ratio of 1:0.5~1:10 as a precursor.

[0024] Furthermore, in the second mixing step, light coking oil and heavy coking oil are mixed as an additive at a mass ratio of 1:0.1 to 1:5.

[0025] Furthermore, in the kneading step, the precursor and the additive are mixed at a mass ratio of 1:0.01 to 1:0.1 and then kneaded to obtain a paste;

[0026] And / or, the mixing temperature is 80~280℃, the mixing pressure is 0.01~0.1MPa, and the mixing time is 0.5~4.0h.

[0027] Furthermore, the molding process is one of extrusion molding, compression molding, and isostatic pressing.

[0028] And / or, the calcination process involves heating at 800~1200℃ for 12~36 hours;

[0029] And / or, the graphitization process involves heating at 2500-3000℃ for 1-8 hours.

[0030] Furthermore, the softening point of the soft asphalt is 25~55℃, the soft asphalt contains quinoline insolubles, and the mass content of the quinoline insolubles in the soft asphalt is 1~10%; the raw coke contains volatile matter, and the volatile matter content of the raw coke is 3~10%; the precursor contains volatile matter, and the volatile matter content of the precursor is ≥10%.

[0031] Secondly, embodiments of the present invention provide a special type of graphite, which is prepared by the method described in any embodiment of the first aspect.

[0032] By adopting the above technical solution, special graphite with both excellent mechanical properties and low coefficient of thermal expansion can be obtained.

[0033] Furthermore, the flexural strength of the special graphite is 45~60 MPa, and its coefficient of thermal expansion is 2.5×10⁻⁶. -6 °C -1 ~3.3×10 -6 °C -1 . Detailed Implementation

[0034] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Although the description of the present invention is presented in conjunction with preferred embodiments, this does not mean that the features of the invention are limited to these embodiments. On the contrary, the purpose of describing the invention in conjunction with embodiments is to cover other options or modifications that may be derived based on the claims of the present invention. To provide a deep understanding of the invention, many specific details will be included in the following description. The invention may also be implemented without using these details. Furthermore, to avoid confusion or obscuring the focus of the invention, some specific details will be omitted in the description. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of the present invention can be combined with each other.

[0035] To make the objectives, technical solutions, and advantages of the present invention clearer, the embodiments of the present invention will be described in further detail below.

[0036] In this embodiment of the invention, "soft bitumen" refers to the heavy liquid phase fraction obtained by distilling and separating light fractions from high-temperature coal tar.

[0037] In this embodiment of the invention, "bonding coke" refers to the product obtained by coking soft asphalt with a volatile content of 10-40% and a coking value of ≥80%.

[0038] In this embodiment of the invention, "raw coke" refers to coke produced by delayed coking process using residual oil, asphalt or heavy oil as raw materials, which contains sulfur, ash and other substances.

[0039] In this embodiment of the invention, "coking light oil" refers to a low-boiling-point, volatile light oil product that is distilled and separated during the coking process of coal tar or heavy petroleum oil. Specifically, coking light oil typically has a boiling point of 200~300℃, that is, an initial boiling point of 200±5℃.

[0040] In this embodiment of the invention, "coking heavy oil" is the opposite of "coking light oil," and refers to the high-boiling-point, high-viscosity heavy fraction separated during the coking process. Specifically, the boiling point of coking heavy oil is typically 280~400℃, i.e., the initial boiling point is 280±5℃.

[0041] In this embodiment of the invention, "calcined coke" refers to the product of "raw coke" after high-temperature calcination.

[0042] In this embodiment of the invention, "paste" refers to a thermoplastic mixture with plasticity obtained by mixing carbonaceous aggregate with materials having binding properties according to a certain formula.

[0043] In this embodiment of the invention, "pressure" refers to gauge pressure unless otherwise explicitly stated. Specifically, absolute pressure - atmospheric pressure = gauge pressure.

[0044] In a first aspect, embodiments of the present invention provide a method for preparing special graphite, comprising:

[0045] Distillation: Soft pitch is obtained by distilling high-temperature coal tar.

[0046] First coking: The soft asphalt is coked to produce caking coke and coking light oil;

[0047] Second coking: Coking the clumped coke to produce raw coke and coking heavy oil;

[0048] Calcination: Raw coke is calcined in an oxygen-containing atmosphere to obtain calcined coke;

[0049] First mixing: The binder coke and the calcined coke are mixed as a precursor;

[0050] Second mixing: Light coking oil and heavy coking oil are mixed as an additive;

[0051] Mixing: The precursor and additives are mixed and kneaded to obtain a paste;

[0052] Special graphite is obtained by sequentially processing the paste through molding, calcination, and graphitization processes.

[0053] Among them, the bonding coke has volatile matter and coking value. The volatile matter of the bonding coke is 10~40%, and the coking value is ≥80%; the aspect ratio of the calcined coke is ≥1.58.

[0054] This invention uses high-temperature coal tar as a single raw material. By sequentially distilling and coking the high-temperature coal tar twice, it achieves the graded and efficient utilization of each component from the high-temperature coal tar.

[0055] Specifically, the binder coke with specific volatile matter (10-40%) and coking value (≥80%) obtained from the first coking step is introduced into the system as one of the precursors, enabling it to effectively function as a binder in subsequent kneading and calcination processes. Its suitable volatile matter ensures good plasticity and rheological properties of the paste during molding, uniformly wetting and coating the surface of the calcined coke particles. The suitable coking value ensures that the binder coke is fully carbonized and cross-linked during subsequent calcination and high-temperature graphitization treatment, constructing a continuous and dense carbonaceous bonding network between the calcined coke particles, effectively bridging inter-particle porosity defects. Therefore, without the introduction of external reinforcing phases, the mechanical properties of the special graphite can be improved.

[0056] Simultaneously, calcined coke with an aspect ratio ≥1.58, obtained by calcining the green coke from the second coking step in an oxygen-containing atmosphere, is used as aggregate. The oxygen-containing environment creates a gradient porosity structure on the surface of the calcined coke particles, enhancing the interfacial bonding between the calcined coke and the binder coke. The calcined coke forms an overlapping support framework within the special graphite, creating an intrinsically compatible structure with the binder coke. Its high aspect ratio fibrous structure effectively improves the orientation arrangement within the special graphite, endowing it with excellent anisotropy, and thus effectively guiding the directional alignment of graphite crystallites. This results in high flexural strength while reducing the coefficient of thermal expansion of the special graphite. Preferably, the aspect ratio of the calcined coke is ≥1.64, further reducing the coefficient of thermal expansion of the special graphite while ensuring high flexural strength.

[0057] In addition, the coking light oil and coking heavy oil obtained from the same high-temperature coal tar are combined as an additive to further improve the wettability and interfacial compatibility between precursor particles, so that the calcined coke and the bonding coke are more evenly distributed in the kneading process, forming a composite structure with good thermodynamic matching.

[0058] Therefore, without the introduction of an external reinforcing phase, the special graphite obtained has both high flexural strength and low coefficient of thermal expansion. Moreover, the above preparation method realizes closed-loop resource utilization of raw materials, without relying on multiple impregnation-calcination cycles, and the process is simple.

[0059] In this embodiment of the invention, the softening point of the soft asphalt is 25-55°C. The soft asphalt contains quinoline insolubles, with a mass content of 1-10%. This allows the soft asphalt to maintain appropriate melt flow characteristics during the subsequent first coking step. The low softening point range ensures that the soft asphalt fully melts and expands after heating, allowing for sufficient mass transfer reactions of internal components. The moderate content of quinoline insolubles, acting as the primary carbonaceous core, can orderly induce aromatic components to condense into coke during the coking stage, stably generating caking coke and coking light oil with volatile matter content of 10%-30% and a coking value ≥80%. Furthermore, if the softening point of the soft asphalt is 30-40°C and the mass content of quinoline insolubles is 3-5%, this can further reduce the fluctuation range of raw material properties, improve the consistency of caking coke and coking light oil indicators, and reduce the difficulty of controlling production process parameters.

[0060] In this embodiment of the invention, in the first coking step, the coking temperature is 350~450℃, the coking time is 2~8h, and the coking pressure is 0.1~0.3MPa. By coking soft asphalt with a softening point of 25~55℃ and a quinoline insoluble content of 1~10% by mass at 350~450℃ and 0.1-0.3MPa for 2~8h, a binder coke with a volatile matter content of 10~40% and a coking value ≥80% can be obtained. This binder coke further retains an appropriate amount of volatile matter and medium molecular weight aromatic components, giving it both plasticity and high coking properties during subsequent kneading and calcination. This achieves structural homogenization between the binder phase and the aggregate phase and avoids excessive porosity defects caused by excessively high volatile matter content.

[0061] Preferably, in the first coking step, the coking temperature is 390~430℃, the coking time is 4~6h, and the coking pressure is 0.15~0.25MPa. This can weaken the influence of process parameter fluctuations on the volatile matter and coking value of the bonding coke, stably produce highly uniform bonding coke, ensure that the bonding coke fully plays the role of the bonding phase in the entire process of kneading and roasting, and at the same time shorten the ineffective reaction time and reduce the energy consumption of the coking process.

[0062] Furthermore, in the second coking step, the coking temperature is 450~520℃, the coking time is 6~24h, and the coking pressure is 0.1~0.3MPa. Within this range of process parameters, the degree of thermal polycondensation reaction of the bonded coke can be precisely controlled, adapting to the reaction requirements for preparing green coke through secondary coking of the bonded coke. This avoids excessive cracking or excessive cross-linking and carbonization of the aromatic chains of the bonded coke macromolecules, and allows for controllable regulation of the microfiber morphology and grain regularity of the prepared green coke. Among these factors, a suitable coking temperature can provide sufficient activation energy for the condensation polymerization and cyclization of aromatic hydrocarbon macromolecules to synthesize long-chain fibrous carbon structures, avoiding the problems of incomplete condensation reaction, severe coke blockage, and low fiber forming rate caused by excessively low temperature. At the same time, it avoids the defects of thermal fracture of carbon structure, coke fiber breakage, and substandard aspect ratio caused by excessively high temperature. Appropriate coking time can ensure that the internal components of the bonded coke are fully and deeply coked, ensuring the homogeneity and stability of the coke structure. Maintaining a slightly positive pressure range can suppress the disorderly volatilization and loss of light components in coking, ensuring the stability of the system reaction environment, and simultaneously improving the yield of coking heavy oil.

[0063] Preferably, in the second coking step, the coking temperature is 480~500℃ and the coking time is 8~16h. This reduces the impact of process parameter fluctuations on the morphology and internal density of the raw coke fibers, improves the orientation of the raw coke fibers, and makes the subsequent calcined coke fiber scaffold structure more regular. At the same time, it shortens the ineffective coking reaction time, reduces the energy consumption of the coking process, improves the stability of the two-stage coking component output, and ensures batch consistency of the final special graphite's flexural strength and coefficient of thermal expansion.

[0064] In this embodiment of the invention, the first coking step and the second coking step are continuous coking processes, with the temperature rising from the first coking step to the second coking step at a rate ≥40℃ / h. By controlling the heating rate, a unique "airflow shear ordering" effect is formed. The shear stress field generated by the rapid escape of small molecule volatiles can induce the orientation and alignment of mesophase molecules, thereby helping to further reduce the thermal expansion coefficient of the special graphite. Preferably, the heating rate is ≥60℃ / h, further enhancing the directional control effect of the thermal reaction and ensuring that the mechanical properties and thermal expansion coefficient of the special graphite are uniform and controllable.

[0065] In the above embodiments, the obtained coke has volatile matter, and the volatile matter content of the coke is 3 to 10%.

[0066] In this embodiment of the invention, the calcination temperature is 1000~1500℃ and the calcination time is 0.5~8.0h. By calcining in an aerobic environment and controlling the calcination temperature and time, controllable oxidation etching is formed on the surface of the calcined coke particles. Open pores are formed on the surface of the raw coke particles, while the interior remains relatively dense. This ensures sufficient wetting of the obtained calcined coke and the binder coke, while avoiding excessive oxidation that would reduce the strength of the calcined coke. At the same time, the introduction of oxygen-containing functional groups further enhances the interfacial compatibility and bonding force between the calcined coke and the binder coke.

[0067] In the above embodiments, the aspect ratio of 1-2 mm particles in the calcined coke is ≥1.58, the strength modulus of 1-2 mm particles is ≥55%, and the true density is ≥1.96 g / cm³. 3 Preferably, the aspect ratio of the calcined coke is ≥1.68, which is beneficial to further reduce the coefficient of thermal expansion of the special graphite.

[0068] Preferably, the calcination temperature is 1100~1300℃, and the calcination time is 2.0~4.0h. Within this preferred temperature range, it is beneficial to fully remove volatiles while maximally preserving and optimizing the microcrystal development orientation and structural uniformity of the calcined coke. Simultaneously, the preferred calcination time enables dual optimization of the true density and resistivity of the calcined coke, giving it superior oxidation resistance and high-temperature thermal stability. Furthermore, this preferred process condition significantly reduces the single-batch production cycle and substantially lowers heat energy consumption while ensuring sufficient calcination. It also effectively eliminates batch-to-batch quality fluctuations caused by insufficient or over-calcination.

[0069] In the embodiments of the present invention, in the first mixing step, the bonding coke and the calcined coke are crushed and ground respectively until the particle size D50 of the bonding coke is ≤5μm and the particle size of the calcined coke is 5~500μm. Then, they are mixed at a mass ratio of 1:0.5~1:10 as a precursor. The obtained precursor has volatile matter, and the volatile matter of the precursor is ≥10%.

[0070] In the above embodiments, the binder coke, with a particle size of D50≤5μm, possesses excellent dispersibility and surface activity. This allows it to fully and uniformly wet and tightly coat the surface of the calcined coke particles during the kneading process, effectively avoiding localized agglomeration or coating blind spots caused by excessively large binder coke particles. This enables the construction of a continuous and dense carbonaceous bonding network between the calcined coke particles in the subsequent calcination process, further reducing interfacial porosity and microstructural defects. Simultaneously, the calcined coke with a particle size of 5~500μm, acting as aggregate, forms a reasonable multi-level particle size distribution with the binder coke, achieving close packing between particles. This provides a robust supporting framework for the interior of the special graphite and effectively increases the density of the green body. Furthermore, the mass ratio of binder coke to calcined coke is controlled at 1:0.5~1:10, precisely controlling the dynamic balance between the binder phase and the aggregate phase. This avoids insufficient interfacial bonding strength and loose structure caused by an excessively low proportion of binder coke, while also preventing macroscopic porosity and microcracks caused by severe shrinkage and concentrated escape of volatiles during high-temperature calcination and graphitization due to an excessively high proportion. This synergistic design of particle size parameters and proportions not only improves the bulk density and flexural strength of the special graphite, but also complements the directional orientation effect of the high aspect ratio calcined coke aggregate, further ensuring that the special graphite maintains a stable low coefficient of thermal expansion while possessing high strength.

[0071] In this embodiment of the invention, in the second mixing step, light coking oil and heavy coking oil are mixed at a mass ratio of 1:0.1 to 1:5 as an additive. Within the above mass ratio range, light coking oil has a lower viscosity, which can effectively reduce the overall viscosity of the system and promote its penetration and wetting of powder particles; heavy coking oil has a higher viscosity and coking value, which gives the paste suitable cohesive force and molding stability. The appropriate ratio of the two improves the interfacial compatibility and kneading uniformity between precursor particles. In addition, since the additives are homologous, they are derived from coking by-products in this preparation method and have the same aromatic structure as the binder coke and calcined coke, realizing the homogenization of "raw material-additive-product". Phenolic and quinoline nitrogen / oxygen heterocyclic compounds in the additives act as surface-active components, reducing interfacial tension and promoting the spreading of the binder phase on the aggregate surface; methylnaphthalene, acenaphthene, fluorene and other components have similar molecular weight distributions to the low-temperature coking products of the binder coke, forming a homogeneous swelling system at the kneading temperature and eliminating the phase interface. During the subsequent roasting process, the additive not only plays a role in plasticizing and reducing viscosity, but its heavy components can also undergo deep thermal condensation and participate in the construction of carbon network, further bridging the pores between particles, thereby improving the bulk density and mechanical strength of special graphite, and realizing the closed-loop resource utilization of all components of high-temperature coal tar.

[0072] Specifically, the additives are composed of one or more compounds consisting of 1-4 benzene rings and nitrogen-oxygen-sulfur heterocyclic aromatic rings. Exemplarily, the additives include one or more of phenol, quinoline, isoquinoline, indole, naphthalene, methylnaphthalene, biphenyl, dimethylnaphthalene, acenaphthene, fluorene, anthracene, phenanthrene, carbazole, pyrene, benzo[a]phenanthrene, and benzo[a]pyrene. By mass percentage, the coking light oil comprises: 20-25% naphthalene, 10-15% β-methylnaphthalene, 10-15% acenaphthene, 5-10% α-methylnaphthalene, 5-10% indene, 3-5% fluorene, 2-5% thionindene, 2-5% quinoline, 2-5% indole, 2-5% indene, 2-5% biphenyl, 2-5% 2,6-dimethylnaphthalene, and 2-5% 2,3-dimethylnaphthalene. By mass percentage, coking heavy oil comprises: 22-25% phenanthrene, 20-25% anthracene, 9-12% fluoranthene, 8-12% fluorene, 7-10% acenaphthene, 3-6% 2-methylanthracene, 3-6% 1-methylphenanthrene, and 0-5% naphthalene.

[0073] In this embodiment of the invention, during the kneading step, the precursor and additives are mixed at a mass ratio of 1:0.01 to 1:0.1 and then kneaded to obtain a paste. Within this mass ratio range, on the one hand, the additives can fully coat the precursor, effectively weakening the agglomeration of the binder coke powder, improving the wettability of the interface between the calcined coke and the binder coke, allowing the binder coke to be better dispersed and slid evenly on the surface and in the gaps of the calcined coke, thereby giving the paste excellent plasticity and ensuring the smooth progress of subsequent molding processes. On the other hand, it effectively avoids the large amount of volatiles released during subsequent calcination and high-temperature graphitization treatment due to excessive light components. At this mass ratio, the paste obtained by kneading not only has uniform dispersion of each component and high thermodynamic matching, but also forms a dense and continuous carbonaceous skeleton after high-temperature carbonization, further ensuring the high bulk density, high flexural strength, and excellent structural stability of the final special graphite.

[0074] Furthermore, the kneading temperature is 80~280℃, the kneading pressure is 0.01~0.1MPa, and the kneading time is 0.5~4.0h. Within this temperature range, the additive components in the kneading system can be fully softened and their viscosity reduced. Simultaneously, the surface activity of the binder particles in the precursor is effectively activated, allowing the solid-liquid two phases to rapidly wet, diffuse, and interface-bind under moderate thermal energy. This ensures that the paste acquires sufficient plastic flow capacity during kneading for uniform mixing, thus ensuring that the material remains in a homogeneous and stable state throughout the kneading process. Within this pressure range, it prevents the lightweight components from undergoing violent vaporization and escape due to localized overheating at the kneading temperature, reducing porosity defects within the paste and improving its packing density. Combined with this kneading time, it ensures thorough and uniform mixing of all components, eliminates localized agglomeration and dry spots, while avoiding material structure damage and increased energy consumption caused by excessive shear friction. Therefore, the coordinated control of temperature, pressure and time can produce a paste with excellent rheological properties, uniform component distribution and tight interfacial bonding, providing a good plastic basis for subsequent molding processes and effectively reducing volume shrinkage and defect generation during subsequent high-temperature calcination, thereby ensuring the structural density and mechanical properties of special graphite.

[0075] In the above embodiments, the forming process is one of extrusion molding, compression molding, and isostatic pressing. By selecting any one of these processes to process the paste, the requirements for preparing special graphite products of different specifications and under different operating conditions can be met, offering flexibility in process selection. Furthermore, in extrusion molding, the paste undergoes directional rheology along the extrusion direction under the extrusion pressure, further enhancing the directional arrangement of the calcined coke, amplifying the anisotropic advantages brought by the high aspect ratio of the calcined coke, and promoting the regular arrangement of graphite microcrystals along the extrusion orientation. This improves the flexural strength of the graphite products while further reducing the coefficient of thermal expansion.

[0076] In this embodiment of the invention, the calcination process involves heating at 800-1200℃ for 12-36 hours. In other words, the calcination temperature of 800-1200℃ and the calcination time of 12-36 hours can construct a dense, continuous, and structurally stable carbonaceous skeleton, improve the bulk density and mechanical strength of the calcined green body obtained by the calcination process, and provide a calcined green body with excellent physicochemical properties for subsequent graphitization processes.

[0077] In this embodiment of the invention, the graphitization process involves heating at 2500-3000℃ for 1-8 hours. In other words, the graphitization temperature of 2500-3000℃ and the graphitization time of 1-8 hours provide sufficient activation energy for the fused ring aromatic sheets inside the carbon matrix, driving the amorphous carbon structure to rearrange and become regular, gradually forming an ordered stacked graphite microcrystalline structure. This fully utilizes the directional induction effect of the high aspect ratio fiber skeleton of the calcined coke, allowing the microcrystals to grow orderly along the aggregate arrangement direction, simultaneously improving the graphitization degree and mechanical bending strength of the special graphite while suppressing the increase in the coefficient of thermal expansion.

[0078] Secondly, embodiments of the present invention provide a special type of graphite, which is prepared by the method described in any embodiment of the first aspect.

[0079] By adopting the above technical solution, special graphite with both excellent mechanical properties and low coefficient of thermal expansion can be obtained.

[0080] In the above embodiments, the flexural strength of the special graphite is 45~60 MPa, and the coefficient of thermal expansion of the special graphite is 2.5×10⁻⁶ MPa. -6 ~3.3×10 -6 °C -1 This meets the high standards of advanced specialty graphite, which requires graphite products to possess both excellent mechanical properties and a low coefficient of thermal expansion.

[0081] The following will describe the implementation method in more detail.

[0082] Example 1

[0083] A method for preparing a special type of graphite is provided, comprising:

[0084] Distillation step: High-temperature coal tar is distilled to obtain soft pitch with a softening point of 34℃ and a quinoline insoluble content of 3.2% by mass;

[0085] First coking step: Soft asphalt is coked at 430℃ and 0.2MPa for 4 hours to obtain viscous coke with volatile matter of 27% and coking value of 87% and coking light oil.

[0086] The second coking step involves coking the brittle coke at 485℃ and 0.25MPa for 12 hours to obtain raw coke and coking heavy oil with a volatile content of 5%. The temperature is increased from 430℃ in the first coking step to 485℃ in the second coking step at a rate of 90℃ / h.

[0087] Calcination steps: Raw coke is calcined at 1200℃ for 3.0 h in an oxygen-containing atmosphere to obtain calcined coke with an aspect ratio of 1.68; the calcined coke contains 1-2 mm particles with an aspect ratio of 1.68, a strength modulus of 55% for the 1-2 mm particles, and a true density of 2.03 g / cm³. 3 ;

[0088] First mixing step: The bonded coke and calcined coke are crushed and ground separately until the particle size D50 of the bonded coke is 3.8 μm and the particle size of the calcined coke is 5~500 μm. The bonded coke and calcined coke are then mixed at a mass ratio of 1:2 as a precursor. The volatile matter content of the precursor is 18%.

[0089] The second mixing step: Light coking oil and heavy coking oil are mixed at a mass ratio of 1:0.5 as an additive;

[0090] Mixing step: Mix the precursor and additives at a mass ratio of 1:0.05 and knead at 150℃ and 0.05MPa for 2.0h to obtain a paste;

[0091] The paste was extruded into small rods and then subjected to calcination and graphitization processes. The calcination temperature was 970℃ and the calcination time was 24 h. The graphitization temperature was 2800℃ and the graphitization time was 2 h, thus producing special graphite.

[0092] The flexural strength and coefficient of thermal expansion of the special graphite obtained in Example 1 are shown in Table 1.

[0093] Example 2

[0094] A method for preparing a special type of graphite is provided, comprising:

[0095] Distillation step: High-temperature coal tar is distilled to obtain soft pitch with a softening point of 34℃ and a quinoline insoluble content of 3.2% by mass;

[0096] First coking step: The soft asphalt is coked at 380℃ and 0.2MPa for 6 hours to obtain viscous coke with volatile matter of 35% and coking value of 81% and coking light oil.

[0097] The second coking step involves coking the brittle coke at 485℃ and 0.25MPa for 12 hours to obtain raw coke and coking heavy oil with a volatile content of 6%. The temperature is increased from 380℃ in the first coking step to 485℃ in the second coking step at a rate of 90℃ / h.

[0098] Calcination steps: Raw coke is calcined at 1200℃ for 3.0 h in an oxygen-containing atmosphere to obtain calcined coke with an aspect ratio of 1.67; the calcined coke contains 1-2 mm particles with an aspect ratio of 1.67, a strength modulus of 56% for the 1-2 mm particles, and a true density of 2.03 g / cm³. 3 ;

[0099] First mixing step: The bonded coke and calcined coke are crushed and ground separately until the particle size D50 of the bonded coke is 3.9 μm and the particle size of the calcined coke is 5~500 μm. The bonded coke and calcined coke are then mixed at a mass ratio of 1:1.75 as a precursor. The volatile matter content of the precursor is 18%.

[0100] The second mixing step: Light coking oil and heavy coking oil are mixed at a mass ratio of 1:0.5 as an additive;

[0101] Mixing step: Mix the precursor and additives at a mass ratio of 1:0.05 and knead at 150℃ and 0.05MPa for 2.0h to obtain a paste;

[0102] The paste was extruded into small rods and then subjected to calcination and graphitization processes. The calcination temperature was 970℃ and the calcination time was 24 h. The graphitization temperature was 2800℃ and the graphitization time was 2 h, thus producing special graphite.

[0103] The flexural strength and coefficient of thermal expansion of the special graphite obtained in Example 2 are shown in Table 1.

[0104] Example 3

[0105] A method for preparing a special type of graphite is provided, comprising:

[0106] Distillation step: High-temperature coal tar is distilled to obtain soft pitch with a softening point of 34℃ and a quinoline insoluble content of 3.2% by mass;

[0107] First coking step: Soft asphalt is coked at 430℃ and 0.2MPa for 4 hours to obtain viscous coke with volatile matter of 27% and coking value of 87% and coking light oil.

[0108] The second coking step involves coking the brittle coke at 485℃ and 0.25MPa for 12 hours to obtain raw coke and coking heavy oil with a volatile content of 5%. The temperature is increased from 430℃ in the first coking step to 485℃ in the second coking step at a rate of 60℃ / h.

[0109] Calcination steps: Raw coke is calcined at 1200℃ for 3.0 h in an oxygen-containing atmosphere to obtain calcined coke with an aspect ratio of 1.64; the calcined coke contains 1-2 mm particles with an aspect ratio of 1.64, a strength modulus of 54% for the 1-2 mm particles, and a true density of 2.02 g / cm³. 3 ;

[0110] First mixing step: The bonded coke and calcined coke are crushed and ground separately until the particle size D50 of the bonded coke is 3.7 μm and the particle size of the calcined coke is 5~500 μm. The bonded coke and calcined coke are then mixed at a mass ratio of 1:2.0 as a precursor. The volatile matter content of the precursor is 19%.

[0111] The second mixing step: coking light oil and coking heavy oil are mixed at a mass ratio of 1:0.5 as an additive;

[0112] Mixing step: Mix the precursor and additives at a mass ratio of 1:0.05 and knead at 150℃ and 0.05MPa for 2.0h to obtain a paste;

[0113] The paste was extruded into small rods and then subjected to calcination and graphitization processes. The calcination temperature was 970℃ and the calcination time was 24 h. The graphitization temperature was 2800℃ and the graphitization time was 2 h, thus producing special graphite.

[0114] The flexural strength and coefficient of thermal expansion of the special graphite obtained in Example 3 are shown in Table 1.

[0115] Example 4

[0116] A method for preparing a special type of graphite is provided, comprising:

[0117] Distillation step: High-temperature coal tar is distilled to obtain soft pitch with a softening point of 34℃ and a quinoline insoluble content of 3.2% by mass;

[0118] First coking step: The soft asphalt is coked at 380℃ and 0.2MPa for 6 hours to obtain viscous coke with volatile matter of 35% and coking value of 81% and coking light oil.

[0119] The second coking step involves coking the brittle coke at 485℃ and 0.25MPa for 12 hours to obtain raw coke and coking heavy oil with a volatile content of 6%. The temperature is increased from 380℃ in the first coking step to 485℃ in the second coking step at a rate of 60℃ / h.

[0120] Calcination steps: Raw coke is calcined at 1200℃ for 3.0 h in an oxygen-containing atmosphere to obtain calcined coke with an aspect ratio of 1.63; the calcined coke contains 1-2 mm particles with an aspect ratio of 1.63, a strength modulus of 57% for the 1-2 mm particles, and a true density of 2.03 g / cm³. 3 ;

[0121] First mixing step: The bonded coke and calcined coke are crushed and ground separately until the particle size D50 of the bonded coke is 3.9 μm and the particle size of the calcined coke is 5~500 μm. The bonded coke and calcined coke are then mixed at a mass ratio of 1:1.75 as a precursor. The volatile matter content of the precursor is 19%.

[0122] The second mixing step: coking light oil and coking heavy oil are mixed at a mass ratio of 1:0.5 as an additive;

[0123] Mixing step: Mix the precursor and additives at a mass ratio of 1:0.05 and knead at 150℃ and 0.05MPa for 2.0h to obtain a paste;

[0124] The paste was extruded into small rods and then subjected to calcination and graphitization processes. The calcination temperature was 970℃ and the calcination time was 24 h. The graphitization temperature was 2800℃ and the graphitization time was 2 h, thus producing special graphite.

[0125] The flexural strength and coefficient of thermal expansion of the special graphite obtained in Example 4 are shown in Table 1.

[0126] Comparative Example 1

[0127] A method for preparing a special type of graphite is provided, comprising:

[0128] Distillation step: High-temperature coal tar is distilled to obtain soft pitch with a softening point of 34℃ and a quinoline insoluble content of 3.2% by mass;

[0129] First coking step: Soft asphalt is coked at 430℃ and 0.2MPa for 4 hours to obtain viscous coke with volatile matter of 27% and coking value of 87% and coking light oil.

[0130] First mixing step: The bonded coke and the calcined coke with an aspect ratio of 1.57 are crushed and ground separately until the particle size D50 of the bonded coke is 3.9 μm and the particle size of the calcined coke is 5~500 μm. The bonded coke and the calcined coke are then mixed at a mass ratio of 1:1 as a precursor. The volatile matter content of the precursor is 15%.

[0131] Second mixing step: The coking light oil and the coking heavy oil in Example 1 are mixed at a mass ratio of 1:0.5 as an additive;

[0132] Mixing step: Mix the precursor and additives at a mass ratio of 1:0.05 and knead at 150℃ and 0.05MPa for 2.0h to obtain a paste;

[0133] The paste was extruded into small rods and then subjected to calcination and graphitization processes. The calcination temperature was 970℃ and the calcination time was 24 h. The graphitization temperature was 2800℃ and the graphitization time was 2 h, thus producing special graphite.

[0134] The flexural strength and coefficient of thermal expansion of the special graphite obtained in Comparative Example 1 are shown in Table 1.

[0135] Comparative Example 2

[0136] A method for preparing a special type of graphite is provided, comprising:

[0137] First mixing step: Commercially available asphalt from Baowu Carbon Industry with a volatile matter content of 53% and a coking value of 58% is used as a binder, and calcined coke from Example 1 is used as aggregate; BG130 asphalt and calcined coke are mixed at a mass ratio of 1:0.05 as a precursor, and the volatile matter content of the precursor is 24%;

[0138] Mixing step: Using the additives in Example 1, the precursor and additives were mixed at a mass ratio of 1:0.05 and then kneaded at 150°C and 0.05MPa for 2.0h to obtain a paste;

[0139] The paste was extruded into small rods and then subjected to calcination and graphitization processes. The calcination temperature was 970℃ and the calcination time was 24 h. The graphitization temperature was 2800℃ and the graphitization time was 2 h, thus producing special graphite.

[0140] The flexural strength and coefficient of thermal expansion of the special graphite obtained in Comparative Example 2 are shown in Table 1.

[0141] Table 1:

[0142]

[0143] As shown in Table 1, compared with the comparative example, the special graphite in the embodiments of the present invention has both high flexural strength and low coefficient of thermal expansion.

[0144] To facilitate understanding of the present invention, the following parameter testing methods are described:

[0145] Flexural strength: The test method is in accordance with GB / T 3074.1-2021.

[0146] Coefficient of thermal expansion: Test methods refer to GB / T 3074.4-2016 and YB / T 6046-2022.

[0147] While the present invention has been described with reference to certain preferred embodiments, those skilled in the art should understand that the above description is a further detailed explanation of the invention in conjunction with specific embodiments, and should not be construed as limiting the specific implementation of the invention to these descriptions. Various changes in form and detail can be made by those skilled in the art, including several simple deductions or substitutions, without departing from the spirit and scope of the invention.

Claims

1. A method for preparing a special type of graphite, characterized in that, include: Distillation: Soft pitch is obtained by distilling high-temperature coal tar. First coking: The soft asphalt is coked to obtain caking coke and coking light oil; Second coking: The bonded coke is coked to obtain raw coke and coking heavy oil; Calcination: The raw coke is calcined in an oxygen-containing atmosphere to obtain calcined coke; First mixing: The bonding coke and the calcined coke are mixed as a precursor; Second mixing: The light coking oil and the heavy coking oil are mixed as an additive; Mixing: The precursor and the additive are mixed and kneaded to obtain a paste; The paste is sequentially subjected to a molding process, a calcination process, and a graphitization process to obtain special graphite. The bonding coke has volatile matter and coking value, wherein the volatile matter of the bonding coke is 10~40% and the coking value is ≥80%; and the aspect ratio of the calcined coke is ≥1.

58.

2. The preparation method according to claim 1, characterized in that, In the first coking step, the coking temperature is 350~450℃, the coking time is 2~8h, and the coking pressure is 0.1~0.3MPa.

3. The preparation method according to claim 2, characterized in that, In the second coking step, the coking temperature is 450~520℃, the coking time is 6~24h, and the coking pressure is 0.1~0.3MPa.

4. The preparation method according to claim 3, characterized in that, The temperature is increased from the temperature in the first coking step to the temperature in the second coking step, and the rate of increase is ≥40℃ / h.

5. The preparation method according to claim 1, characterized in that, In the calcination step, the calcination temperature is 1000~1500℃, and the calcination time is 0.5~8h.

6. The preparation method according to claim 1, characterized in that, In the first mixing step, the binder coke and the calcined coke are respectively crushed and ground to a particle size D of the binder coke. 50 After the particle size of the calcined coke is ≤5μm and the particle size of the calcined coke is 5~500μm, it is mixed at a mass ratio of 1:0.5~1:10 as a precursor.

7. The preparation method according to claim 6, characterized in that, In the second mixing step, the light coking oil and the heavy coking oil are mixed at a mass ratio of 1:0.1 to 1:5 as an additive.

8. The preparation method according to claim 7, characterized in that, In the kneading step, the precursor and the additive are mixed at a mass ratio of 1:0.01 to 1:0.1 and then kneaded to obtain a paste. And / or, the mixing temperature is 80~280℃, the mixing pressure is 0.01~0.1MPa, and the mixing time is 0.5~4.0h.

9. The preparation method according to claim 1, characterized in that, The molding process is one of extrusion molding, compression molding, and isostatic pressing. And / or, the calcination process involves heating at 800~1200℃ for 12~36 hours; And / or, the graphitization process involves heating at 2500-3000℃ for 1-8 hours.

10. The preparation method according to claim 1, characterized in that, The softening point of the soft asphalt is 25~55℃, the soft asphalt contains quinoline insolubles, and the mass content of the quinoline insolubles in the soft asphalt is 1~10%; the raw coke contains volatile matter, and the volatile matter content of the raw coke is 3~10%; the precursor contains volatile matter, and the volatile matter content of the precursor is ≥10%.

11. A special type of graphite, characterized in that, It is prepared by the preparation method according to any one of claims 1-10.

12. The special graphite as described in claim 11, characterized in that, The special graphite has a flexural strength of 45~60 MPa and a coefficient of thermal expansion of 2.5×10⁻⁶ MPa. -6 °C -1 ~3.3×10 -6 °C -1 .

Citation Information

Patent Citations

  • Preparation process for preparing isostatic pressing special graphite product from artificial graphite powder and application

    CN122010566A